Exploring the Influence of Beliefs of Instructors on Adoption of Technology in Teaching - Hasan, Zahir (Indonesian Journal of EFL and Linguistics, 2021)
The implementation of Emergency Remote Teaching (ERT) due to Covid-19 pandemic resulted in classes being taught online.  This research study examines computer-mediated instruction as it is influenced by beliefs of English-language instructors, and how those instructors make sense of their beliefs regarding computer-mediated online instruction tools.  An Interpretative Phenomenological Analysis (IPA) research design was used.  English-language instructors employed full-time in universities in Tokyo participated in this study.  It appeared that each instructor’s beliefs interacted in a complex manner to technology which impacted instructors’ teaching practices related to the use of computer-mediated instruction.  It revealed a multifaceted relationship between what instructors’ think and what they do in class in relation to computer-mediated tasks.  Findings of this study suggest that English language instructors are navigating competently, yet cautiously in the digital age.  This study suggests technology integration into the English language curriculum will require a greater collaborative effort by relevant stakeholders in recognizing instructors’ beliefs as vital to technology acceptance